Deformation of Implant Abutments After Framework Connection Using Strain Gauges - Hollweg, Henrique; Jacques, Leticia Borges; Moura, Marcio da Silva [UNESP]; Bianco, Vinicius Cappo; Sousa, Edson Antonio Capello [UNESP]; Rubo, Jose Henrique (Allen Press Inc, 2012)
When a cylinder is connected to an abutment it is expected that abutment and cylinder will be subjected to compression forces throughout their periphery because of the clamping force exerted by the screw. The deformation resultant of this compression should be measurable and uniform along the periphery of the abutment. Considering that multiple retainers connected to each other can affect the fit of a framework, as well as the use of different alloys, it is expected that the abutments will present different levels of deformation as a result of framework connection. The aim of this study was to evaluate the deformation of implant abutments after frameworks, cast either in cobalt-chromium (CoCr) or silver-palladium (AgPd) alloys, were connected. Samples (n = 5) simulating a typical mandibular cantilevered implant-supported prosthesis framework were fabricated in cobalt-chromium and silver-palladium alloys and screwed onto standard abutments positioned on a master-cast containing 5 implant replicas. Two linear strain gauges were fixed on the mesial and distal aspects of each abutment to capture deformation as the retention screws were tightened. A combination of compressive and tensile forces was observed on the abutments for both CoCr and AgPd frameworks. There was no evidence of significant differences in median abutment deformation levels for 9 of the 10 abutment aspects. Visually well-fit frameworks do not necessarily transmit load uniformly to abutments. The use of CoCr alloy for implant-supported prostheses frameworks may be as clinically acceptable as AgPd alloy.
Keywords: implant frameworks; prosthesis fit; strain gauges